ANALYSIS OF THE RESPONSE OF COFFEE BEVERAGE BUSINESS ACTORS TO THE OBLIGATION OF HALAL CERTIFICATION IN PANYABUNGAN MANDAILING NATAL - Jureid (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This research method is descriptive qualitative research, namely research that describes certain situations based on facts in the field. The aim of this research is to find out how coffee business actors respond to the obligation of halal certification. The results of this research show that there are several types of responses given by coffee shop business actors regarding the obligation to halal certification. The results of the analysis regarding the responses given by coffee shop business actors to the halal certification obligation are as follows: Responses include knowledge, information, and skills. all sources have different levels of knowledge regarding halal certificates. One of the sources knew a lot about halal certificates, and the other sources were considered to still have minimal knowledge about halal certificates. Responses related to an individual's attitudes, emotions, and assessment of something. All resource persons supported and were motivated to carry out halal certification, because they were aware of the various positive benefits that would be obtained. Responses related to behavior. All coffee shop business actors still seem hesitant about carrying out halal certification because they don't know the details of the Halal Product Guarantee Law. Future suggestions for the government are to immediately overcome the problems that are hampering the implementation of the Halal Product Guarantee Law so that business actors immediately carry out halal certification. For business actors to maintain the quality and halalness of the products they sell so that consumers feel safe when consuming these products.